The Impact of Different Types of Conflict on the U.S. Dollar Exchange Rate - Syavera, Venita; Alfarisi, Salman (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
Fluctuations in the dollar exchange rate reflect the macroeconomic dynamics experienced by a country. Exchange rate instability is often triggered by external factors, one of which is socio-political conflicts such as wars, violence against civilians, explosions, and protests. This study aims to examine the impact of various types of conflicts on the changes in USD-IDR in Indonesia. The research was conducted using data from 2015–2022 and applying the Generalized Linear Model (GLM) approach, specifically Poisson regression with a log link function, which is deemed appropriate for count-type data that do not follow a normal distribution. Exchange rate data was obtained from Badan Pusat Statistik (BPS), while conflict data came from the Armed Conflict Location Event Data (ACLED) database. The independent variables analyzed include the categories of war, civil violence, explosions, and protests. The estimation results show that war has a significant negative impact on the exchange rate, while incidents of explosions and protests have a significant positive impact. On the other hand, civil violence has not been statistically proven to have an impact. The results of this study indicate that not all types of conflict have the same impact on exchange rates, making it important for policymakers to identify and differentiate types of conflict in economic analysis. This study opens up opportunities for further research by incorporating other macroeconomic variables and cross-country comparative approaches.